Structure conduct and performance of sesame market in Guraferda and Meinit Goldia District Southwest Ethiopia - Gebre, Engida; Workiye, Agegnehu; Haile; Kassa Tarekegn, Kusse (British Journal of Marketing Studies, 2021)
Sesame is an essential cash crop and plays vital role in the livelihood of many people in Ethiopia. However, sesame production and productivity is not comparable with the productivity of other region in the country. Therefore, this study was initiated to identify sesame market chain actors and their roles, analyze structure-conduct - performance of sesame market and identify constraints of sesame production and marketing in the study area. A multistage sampling techniques was used for sample selection. Total of 270 sesame producing sample households and 17 traders were surveyed. Data obtained through the use of a structured questionnaire were analyzed using structured conduct performance model and descriptive statics. Both primary and secondary sources of data were used. The result of CR4 shows that the top four sesame traders in Biftu and Bachuma market handled 78.36% and 50.21% of the sesame purchased, respectively. This result indicated sesame markets in both districts was strongly oligopolistic market type. The results also revealed that there is imperfect flow of information, traders licensing problems and their subsequent inability to compete with the unlicensed traders are identified to be the major entry and exit barriers to sesame market suggesting that the structure of the sesame market was strong oligopoly. The finding suggests that, to change existing oligopoly market structure in to competitive market structure the government should invest on rural infrastructure; introducing yield increasing technologies; strengthening Institutions that could provide timely market information; Forming primary cooperative; strengthening extension system through training in all aspect and design financial institutions to address the challenges of financial access to smallholder farmers and traders.